2013
DOI: 10.1016/j.matbio.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected new roles for heparanase in Type 1 diabetes and immune gene regulation

Abstract: Heparanase (Hpse) is an endo-β-d-glucuronidase that degrades the glycosaminoglycan heparan sulfate (HS) in basement membranes (BMs) to facilitate leukocyte migration into tissues. Heparanase activity also releases HS-bound growth factors from the extracellular matrix (ECM), a function that aids wound healing and angiogenesis. In disease states, the degradation of HS in BMs by heparanase is well recognized as an invasive property of metastatic cancer cells. Recent studies by our group, however, have identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 53 publications
2
62
0
Order By: Relevance
“…Because these molecules regulate HA binding to CD44, they may affect the phenotypes associated with HA (32). Other components of the ECM are also reported to contribute to the development and progression of insulitis, either through HA-dependent or -independent mechanisms (6,(33)(34)(35)(36)(37). Taken together with our recent work on HA in human T1D (6), the progression to autoimmune diabetes is associated with profound changes in the ECM architecture.…”
Section: Discussionmentioning
confidence: 82%
“…Because these molecules regulate HA binding to CD44, they may affect the phenotypes associated with HA (32). Other components of the ECM are also reported to contribute to the development and progression of insulitis, either through HA-dependent or -independent mechanisms (6,(33)(34)(35)(36)(37). Taken together with our recent work on HA in human T1D (6), the progression to autoimmune diabetes is associated with profound changes in the ECM architecture.…”
Section: Discussionmentioning
confidence: 82%
“…For example, pro-heparanase can induce cell signaling via PI3-kinase-mediated phosphorylation of AKT (38,39) and even act as a transcription factor regulating genes involved in cell differentiation, inflammation, and glucose metabolism (40)(41)(42). Other studies reported that heparanase enzymatic activity upregulates proinflammatory cytokines from human peripheral blood leukocytes (IL-1β, IL-6, IL-8, IL-10, and TNF), as well as mouse splenocytes (IL-6, MCP-1, and TNF) (43).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it has recently been shown that HS is essential for the survival of pancreatic beta cells; In vivo , autoimmune destruction of islets was associated with production of catalytically active heparanase by islet-infiltrating mononuclear cells, and loss of islet HS 25, 26 . Furthermore, treatment with a heparanase inhibitor preserved intra islet HS and protected mice from type I diabetes 25, 26 . Thus, heparanase inhibitors may turn even more important for chronic pancreatitis, protecting beta cell islets from destructive heparanase produced by pancreatic acinar cells (Fig.…”
Section: Discussionmentioning
confidence: 99%